PERBANDINGAN HASIL BELAJAR PESERTA DIDIK SMAN 2 BULUKUMBA YANG DIAJAR MENGGUNAKAN MEDIA MAGIC CARD DAN MEDIA GAME TWISTER - Aswar Anas; Ilyas Ismail; Syahriani Syahriani; Syamsul Syamsul (Al-AHYA: Jurnal Pendidikan Biologi, 2021)
This study focused on students' learning outcomes from SMAN 2 in Bulukumba, who taught with magic cards media and twister games media, and the differences between the two. This quasi-experimental research has a pretest-posttest control group design. The test instrument used in this study consisted of 25 multiple-choice questions. The results showed that students who taught using magic card media were in the high category (57.14%) and very high category (42.86%). The students who taught using the twister game media were in the medium category (8.70%), high (56.52%), and very high (34.78%). According to the independent sample t-test, there was a significant level of 0.089 > 0.05. This indicates that there is no significant difference in learning outcomes between learners who taught using magic cards and learners who taught using game twister media.